2005
DOI: 10.1111/j.1360-0443.2005.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethno‐specific patterns of adolescent tobacco use and the mediating role of acculturation, peer smoking, and sibling smoking

Abstract: This paper demonstrates that disparities in tobacco use among certain ethnic groups can be explained by peer and sibling smoking and acculturation; however, for other ethnic groups, knowledge of the processes that account for differences in tobacco use remains less clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…(See Table 1. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) All papers were reviewed by one author (CG) and by one or more of the other authors, with coding disagreements resolved through discussion. Papers were reviewed against the STROBE Statement 22-item checklist for cross-sectional studies 33 to ensure they were adequately reported.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(See Table 1. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) All papers were reviewed by one author (CG) and by one or more of the other authors, with coding disagreements resolved through discussion. Papers were reviewed against the STROBE Statement 22-item checklist for cross-sectional studies 33 to ensure they were adequately reported.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies were reported on Canadian samples, 20,22,23 with the others conducted in various regions of the US. Three studies were in adolescents or young adults 20,25,31 and the others were based on adults.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have cited a link between psychological risk factors (e.g. depressive symptoms) and cigarette smoking initiation in adolescence [37][38][39][40] . Moreover, we did not investigate the association of the three demographic variables directly to cigarette smoking initiation.…”
Section: Discussionmentioning
confidence: 99%